Hematological ratios as an indicator of severity in alopecia areata: A retrospective nationwide study. - Nicolas Andre; Sarah Weissmann; Bracha Cohen; Chaya Bracha Gordon; Majd Nassar; Inbal Kestenbom; Inbal Golan-Tripto; Amir Horev (PLoS ONE)
Background Alopecia Areata (AA) is an autoimmune condition where the activation of Th1, Th2, and Th17 responses is known to stimulate other white blood cells, potentially affecting hematopoietic lineages. However, previous studies on AA have found no utility in hematological ratios. Our goals were to compare neutrophils-to-lymphocytes ratio (NLR), platelets-to-lymphocytes ratio (PLR), eosinophils-to-lymphocytes ratio (ELR), eosinophils-to-neutrophils ratio (ENR), and eosinophils-to-monocytes ratio (EMR) between patients with AA and controls, as well as between mild and moderate-severe AA cases. Methods and findings We performed a retrospective, population-based cohort study involving adult patients enrolled in the largest national health maintenance organization in Israel. The study comprised 147,020 AA patients and 141,598 healthy controls. AA patients exhibited a higher likelihood of elevated NLR and ELR compared to controls. Upon further classification based on severity, moderate-severe AA patients displayed higher values of NLR, PLR, ELR, and EMR compared to mild AA individuals OR = 1.11 [1.09-1.1], P<0.001; OR = 1.09 [1.05-1.13], P<0.001; OR = 2.06 [1.67-2.53], P<0.001; OR = 1.07 [1.03-1.07)], P<0.001, respectively). Similar trends were observed 12 to 18 months before diagnosis. Conclusion Our results not only deviate from the current literature but also offer a cost-effective, accessible, and efficient tool for enhanced disease prediction and management.